2003
DOI: 10.1093/sysbio/52.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Lizard Family Pygopodidae with Implications for the Diversification of Australian Temperate Biotas

Abstract: We conducted a phylogenetic study of pygopodid lizards, a group of 38 species endemic to Australia and New Guinea, with two major goals: to reconstruct a taxonomically complete and robustly supported phylogeny for the group and to use this information to gain insights into the tempo, mode, and timing of the pygopodid radiation. Phylogenetic analyses of mitochondrial DNA (mtDNA), nuclear DNA (nDNA), and previously published morphological data using parsimony, maximum likelihood, and Bayesian methods on the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 70 publications
4
80
0
Order By: Relevance
“…Since this revision, several additional species and subspecies have been recognized in Western Australia, including D. butleri Storr, 1987, D. haroldi Storr, 1987 andD. fraseri petersoni Shea, 1991. Shea (1991 advocated synonymy of D. haroldi and D. butleri and this view is supported in a recent phylogenetic study of pygopodid lizards by Jennings et al (2003). These authors also elevated D. f. petersoni to full species status and advocated transfer of Ac1ys eoncinna Kluge, 1974 to Delma [as suggested also by Kluge (1976)].…”
Section: Introductionmentioning
confidence: 91%
“…Since this revision, several additional species and subspecies have been recognized in Western Australia, including D. butleri Storr, 1987, D. haroldi Storr, 1987 andD. fraseri petersoni Shea, 1991. Shea (1991 advocated synonymy of D. haroldi and D. butleri and this view is supported in a recent phylogenetic study of pygopodid lizards by Jennings et al (2003). These authors also elevated D. f. petersoni to full species status and advocated transfer of Ac1ys eoncinna Kluge, 1974 to Delma [as suggested also by Kluge (1976)].…”
Section: Introductionmentioning
confidence: 91%
“…An approximately 900-bp segment of coding region was amplified using the following primers; light strand 5'-GCC CAr ACC CCG AAA ATS TTG-3' (modified from Jennings et al 2(03) and heavy 5'-TTA GGG TRG TTA TTT GHC AY A TKC C-3' (Oliver et al 2007b). This fragment of the ND2 gene has been successfully used to examine intrageneric relationships in many diplodactyline gecko groups (Jennings et al 2003;Melville et al 2004;Pepper et al 2006;Bauer et al 2006;Oliver et al 2007a,b). PCR products were amplified using Hotmaster Taq (Eppendorf) using the following conditions: denaturing 94°C, annealling 55°C and for extension noc for 34 amplification cycles.…”
Section: Mitochondrial Dnamentioning
confidence: 99%
“…The A. repens species-group, originally defi ned by Storr et al (1990), now comprises seven species of very similar appearance and that to most fi eld biologists remain diffi cult to distinguish. However, the use of molecular techniques both herein and elsewhere (Jennings et al 2003) has shown that there are clear and distinct genetic divergences among species. These techniques combined with our morphological studies have also demonstrated that the current diversity within the A. repens species-group is underestimated with additional new species.…”
Section: Discussionmentioning
confidence: 77%
“…Smith and Henry (1999) described A. picturata from central inland Western Australia, the fi rst new species for over 20 years. Jennings et al (2003) published a molecular phylogeny for 32 species within the pygopodidae, including all but two of the described species of Aprasia. His study found the genus to be monophyletic when compared to other pygopodid genera and he provided a phylogenetic framework within Aprasia that was mostly concordant with relationships inferred using morphology (Kluge 1974).…”
Section: Introductionmentioning
confidence: 99%